2014
DOI: 10.1109/tsp.2014.2366716
|View full text |Cite
|
Sign up to set email alerts
|

Transient Artifact Reduction Algorithm (TARA) Based on Sparse Optimization

Abstract: Abstract-This paper addresses the suppression of transient artifacts in signals, e.g., biomedical time series. To that end, we distinguish two types of artifact signals. We define "Type 1" artifacts as spikes and sharp, brief waves that adhere to a baseline value of zero. We define "Type 2" artifacts as comprising approximate step discontinuities. We model a Type 1 artifact as being sparse and having a sparse time-derivative, and a Type 2 artifact as having a sparse time-derivative. We model the observed time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Then, we average referenced them. Based on the artifact properties of sparse spikes and step-like discontinuities of the EEG data, we further use Transient Artifact Reduction Algorithm (TARA, the theory will be detailed latter) (Selesnick et al 2014) to clean these artifacts, the results are shown in Fig. 4 below.…”
Section: Preprocessing Module: Eecog_preprocmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we average referenced them. Based on the artifact properties of sparse spikes and step-like discontinuities of the EEG data, we further use Transient Artifact Reduction Algorithm (TARA, the theory will be detailed latter) (Selesnick et al 2014) to clean these artifacts, the results are shown in Fig. 4 below.…”
Section: Preprocessing Module: Eecog_preprocmentioning
confidence: 99%
“…This platform also supports FieldTrip (Oostenveld et al 2011) and EEGLab (Delorme and Scott 2004) data structure. Here, we give further brief introduction to the theory behind TARA (Selesnick et al 2014). The two types of artifacts that TARA is aiming to remove are: sparse spikes (sparse functions) and step-like discontinuities (functions with sparse first derivatives), and the model (for one channel) can be written as:…”
Section: Preprocessing Module: Eecog_preprocmentioning
confidence: 99%
“…This problem can be solved with different approaches, such as alternating direction method of multipliers (ADMM) [34], majorization minimization [35], proximal algorithm [36] and iteratively reweighted least squares minimization [37]. Here we present the formulation using ADMM algorithm.…”
Section: Second Approach: Sparse Decomposition Algorithmmentioning
confidence: 99%
“…proposed here uses a similar technique to recover the lowpass component, but in contrast to LPF/TVD, it is more general -the regularization is more flexible with a tunable parameter, so that LPF/TVD can be considered as a special case. Another algorithm related to the approach taken in this paper is the transient artifact reduction algorithm (TARA) [60] which is utilized to suppress additive piecewise constant artifacts and spikes (similar to a hybrid of Type 2 and Type 3 artifact). The approaches proposed in this work target different types of artifacts (Type 0 and Type 1) and applied in different applications.…”
Section: Related Workmentioning
confidence: 99%